Reduction of intestinal RIPK1 ameliorates HFD-induced metabolic disorders in female mice - Ye Yuan; Xiaomin Hu; Chunguang Guo; Yihua Xu; Shihan Li; Wei Wen; Xinli Hu; Fanxin Zeng; Weiyi Cui; Wenli Chen; Xueting Sun; Ning Hou; et al. (iScience)
Summary: In modern society, excessive nutrient intake from food is a major factor contributing to the development of a series of metabolic disorders and cardiovascular diseases. Further investigation of the mechanisms underlying nutrient absorption in the intestine will help to better understand and develop preventive or therapeutic strategies. In this study, using receptor-interacting protein kinase 1 (Ripk1) intestine-specific heterozygous knockout mice (Ripk1IEC+/−) and high-fat diet (HFD)-feeding mouse model, we report that HFD-induced shift in the transcriptional profile of the ileum toward that of the jejunum, characterized by increased expression of jejunal feature genes in the ileum, are attenuated in Ripk1IEC+/− female mice, but not in males. Accordingly, HFD-induced metabolic disorders, including obesity, impaired glucose tolerance, insulin resistance, and dyslipidemia, are significantly ameliorated in the Ripk1IEC+/− female mice. These findings demonstrate a new, sex-specific intestinal regulatory mechanism and highlight the critical role of intestinal RIPK1 in regulating HFD-induced metabolic disorders in females.